NL ARMS Netherlands Annual Review of Military Studies 2021 Compliance and Integrity in International Military Trade - Beeres, Robert; Bertrand, Robert; Klomp, Jeroen; Timmermans, Job.; Voetelink, Joop.; SpringerLink (Online service) (The Hague : T.M.C. Asser Press : Imprint: T.M.C. Asser Press, 2022)
This is an open access volume of the NL ARMS offers an interdisciplinary view on the domain of Compliance and Integrity in International Military Trade (CIIMT), integrating defence economics, international law, arms export control frameworks and policies, information management, organizational sciences and ethics. Although, in academia, and from an interdisciplinary perspective, CIIMT constitutes a relatively novel research domain, across private and public defence-related sectors, the subject evokes high levels of attention and interest, instigating a need for critical thinking, reflection and creativity to address ensuing multi-faceted issues and problems. The Faculty of Military Sciences at the Netherlands Defence Academy extends an in-house MSc programme on CIIMT, which, by integrating practice-based and scientific-based knowledge, aims to contribute to this need. The MSc programme on CIIMT is concerned with exploring, analysing, understanding, explaining, controlling and improving the military dimension in international military trade. More particularly, CIIMT studies managerial questions regarding strategic trade control of military and dual-use goods and services. CIIMT ties in with the Netherlands Defence Academy$1 (Bs vision on scientific education, embedded in the reflective practitioners' paradigm uniting both management and leadership skills needed to decide and operate in high-tension and high-risk knowledge intensive environments. The Faculty of Military Sciences uses the reflective practitioners$1 (Bparadigm to refer to critical thinking, reflection and Bildung that characterize its thinking doers, the so-called Thinking Soldiers, either at the academic Bachelor$1 (Bs or Master$1 (Bs level. In view of the complexity of the international trade regarding military and dual-use goods and services, the rapid evolvement of strategic trade control and frameworks, and its importance to procurement processes, defence organizations require innovative thinking doers, who, based on an in-depth understanding, from an interdisciplinary perspective can be expected to find - and take responsibility for - creative solutions to problems. NL ARMS 2021 comprises, amongst others, contributions from students and lecturers partaking in this programme. volume of the NL ARMS offers an interdisciplinary view on the domain of Compliance and Integrity in International Military Trade (CIIMT), integrating defence economics, international law, arms export control frameworks and policies, information management, organizational sciences and ethics. Although, in academia, and from an interdisciplinary perspective, CIIMT constitutes a relatively novel research domain, across private and public defence-related sectors, the subject evokes high levels of attention and interest, instigating a need for critical thinking,reflection and creativity to address ensuing multi-faceted issues and problems. The Faculty of Military Sciences at the Netherlands Defence Academy extends an in-house MSc programme on CIIMT, which, by integrating practice-based and scientific-based knowledge, aims to contribute to this need. The MSc programme on CIIMT is concerned with exploring, analysing, understanding, explaining, controlling and improving the military dimension in international military trade. More particularly, CIIMT studies managerial questions regarding strategic trade control of military and dual-use goods and services. CIIMT ties in with the Netherlands Defence Academy$1 (Bs vision on scientific education, embedded in the reflective practitioners' paradigm uniting both management and leadership skills needed to decide and operate in high-tension and high-risk knowledge intensive environments. The Faculty of Military Sciences uses the reflective practitioners$1 (Bparadigm to refer to critical thinking, reflection and Bildung that characterize its thinking doers, the so-called Thinking Soldiers, either at the academic Bachelor$1 (Bs or Master$1 (Bs level. In view of the complexity of the international trade regarding military and dual-use goods and services, the rapid evolvement of strategic trade control and frameworks, and its importance to procurement processes, defence organizations require innovative thinking doers, who, based on an in-depth understanding, from an interdisciplinary perspective can be expected to find - and take responsibility for - creative solutions to problems. NL ARMS 2021 comprises, amongst others, contributions from students and lecturers partaking in this programme. .s
Chapter 1. Introduction -- Chapter 2. Economics of the Arms Trade: What Do We Know? -- Chapter 3. Export Control Regimes - Present-day Challenges and Opportunities -- Chapter 4. Case: Non-compliance at Fokker Services -- Chapter 5. International Export Control Law - Mapping the Field -- Chapter 6. Exploring the Multifaceted Relationship of Compliance and Integrity - The Case of the Defence Industry -- Chapter 7. Do Economic Sanctions Cause Sudden Growth Collapses? -- Chapter 8. Datasets for Combat Aircraft -- Chapter 9. Does Legal Origin Matter for International Arms Control Ratification? -- Chapter 10. Case: Sharing Parts and Services among NATO Partners -- Chapter 11. Limits on the Extraterritoriality of Export Control Legislation -- Chapter 12. Contract Boundary-spanning Governance Initiatives in the International Defense Supply Chain of the F-35 Program -- Chapter 13. Effectiveness of Arms Control: The Case of Saudi Arabia -- Chapter 14. Case: Dronebuster; Handling Non-compliance to ITAR -- Chapter 15. Developing an Adequate Internal Compliance Program for the Royal Netherlands Air Force Command -- Chapter 16. Arms Exports and Export Control of the Dutch Republic 1585-1621.
Accessibility summary: This PDF eBook is produced by a third-party. We have requested that the file be made accessible and compliant with the European Accessibility Act (EAA). However, we have not been able to fully verify its compliance with recognized accessibility standards (such as PDF/UA or WCAG). For detailed accessibility information, please refer to the original publisher$1 (Bs website. If you require an accessible version of this content, please contact accessibilitysupport@springernature.com. We are committed to improving accessibility and will work with the publisher to meet your needs wherever possible.s
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: International law; Human rights; Humanitarian law; Administrative law; Security, International; Politics and war; Public International Law; Human Rights; International Humanitarian Law, Law of Armed Conflict; Administrative Law; International Security Studies; Military and Defence Studies